Predictors of Adverse Events Among Chronic Total Occlusion Patients Undergoing Successful Percutaneous Coronary Intervention and Medical Therapy - Yang L (Dove Medical Press, 2021)
Le Yang,1,2 Lei Guo,1,* Haichen Lv,1 Xiaodong Liu,3 Lei zhong,1 Huaiyu Ding,1 Xuchen Zhou,1 Hao Zhu,1 Rongchong Huang1,4,* 1Department of Cardiology, The First Affiliated Hospital of Dalian Medical University, Dalian City, People’s Republic of China; 2Department of Cardiology, Dalian Third People’s Hospital, Dalian City, People’s Republic of China; 3Department of Radiology, Dalian Friendship Hospital, Dalian City, People’s Republic of China; 4Department of Cardiology, Beijing Friendship Hospital, Capital Medical University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Rongchong Huang; Lei GuoDepartment of Cardiology, The First Affiliated Hospital of Dalian Medical University, 222 Zhongshan Road, Dalian City, 116011, People’s Republic of ChinaTel +86 10-63016616; +86 411-83635963Email rchuang@ccmu.edu.cn; leiguo@dmu.edu.cnObjective: Limited data are available on the predictors of major adverse cardiac events (MACE) after a successful coronary chronic total occlusion (CTO) percutaneous coronary intervention (PCI) and medical therapy. This study aimed to identify predictors of MACE in CTO patients undergoing successful recanalization and medical therapy.Methods: A total of 2015 patients with CTOs were enrolled. About 718 patients underwent successful CTO recanalization, and 1297 patients received medical therapy. The primary outcome was the frequency of MACE, defined as a composite of cardiac death, myocardial infarction, and target-vessel revascularization. Multivariate models were used to determine predictors of MACE.Results: In successful CTO recanalization group, MACE occurred in 123 (17.1%) patients. In multivariate analysis, heart failure (hazard ratio [HR] 1.77, 95% confidence interval [CI]: 1.04– 3.04, p = 0.036) was identified as independent predictors for MACE in successful CTO recanalization. Additionally, in medical therapy group, the significant predictors of MACE were male gender (HR 1.53, 95% CI: 1.13– 2.05, p = 0.005), diabetes mellitus (HR 1.39, 95% CI: 1.11– 1.74, p = 0.003), heart failure (HR 1.44, 95% CI: 1.10– 1.87, p = 0.007), J-CTO score (HR 1.17, 95% CI: 1.07– 1.28, p = 0.001) and multivessel disease (HR 2.20, 95% CI: 1.42– 3.39, p < 0.001).Conclusion: Heart failure was predictor for composite cardiovascular events in patients with CTO after successful recanalization. Male gender, diabetes mellitus, heart failure, J-CTO score and multivessel disease were predictors of MACE in CTO patients with medical therapy.Keywords: coronary chronic total occlusions, percutaneous coronary intervention, medical therapy, predictors, MACE